Investigating the prevalence of contrast-associated nephropathy and the related risk factors in patients undergoing elective angioplasty - Mehrnoush Dianatkhah; Samira Poursaeid; Ehsan Shirvani; Shirinsadat Badri (Wolters Kluwer Medknow Publications, 2023)
Objective: Contrast-associated nephropathy (CAN) is a sudden decrease in kidney function following contrast media administration. Considering the importance of CAN in the patient's outcome and the high prevalence of this complication in cardiac catheterizing centers, this study was designed to investigate the prevalence and the related risk factors of CAN in patients undergoing angioplasty in Chamran Heart Hospital, Isfahan, Iran, from January 2022 to June 2022. Methods: The inclusion criteria were adult patients above 18 admitted for elective percutaneous coronary intervention (PCI). Patient demographic information, underlying diseases and medications, dehydration state, type and amount of contrast media, and serum levels of blood urea nitrogen (BUN) and serum creatinine (SrCr) at 24 and 72 h after contrast injection were all recorded. Findings: Out of 340, 128 patients developed CAN after PCI, giving an incidence of 37.64%. Adjusted analysis showed a significant relation between age over 65, the amount of contrast media administered, and the use of furosemide with the incidence of CAN. However, adjusted logistic regression analysis failed to show any significant relationship between the risk of CAN and the hydration status of the patients at 24 and 48 h after receiving contrast media as diagnosed by BUN/SrCr >20. Conclusion: The prevalence of CAN in this study was higher than in other studies since this high-risk population was under risk factors such as arterial injection of contrast material and a higher amount of contrast material administration. In addition, advanced age, volume of contrast material, and previous or concurrent furosemide administration were associated with an increased risk of CAN.